The Communication Philosophy Model - Jelahut, Felisianus Efrem (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
The aim of this research is to find a model of communication philosophy as a form of relevance to the discourse of ontology, epistemology and axiology. This research uses a qualitative method using a library study approach that uses books or literature as the main source. The library references in the form of books which are primary sources in this research are first, a book entitled On the Philosophy of Communication 1st Edition by Garry Rafford, second, a book entitled Aristotle's Physics Book VIII. The results of this research are a communication philosophy model divided into three sub-models, namely a communication ontology model which is concise about what the formal and material objects of communication science are, a communication epistemology model which discusses how humans acquire knowledge in communication studies and a communication axiology model which focuses on questions regarding what and how the values ​​contained in the messages exchanged in the communication process between the communicator and the communicant.